On Semantic Patterns of “Kill–Verbs” in Modern English - Khachatryan, Robert (Armenian Folia Anglistika, 2013)
The article aims to reveal the semantic structures of the causative verbs in modern English, particularly with reference to the characteristics of the verbs meaning “to kill” and the way of expressing the main meaning of “to cause to die”. More precisely, the present article highlights the semantic features of these verbs that condition their causative nature. The article focuses on the investigation of only those verbs meaning “to cause to die” that are more frequent in speech, particularly the verbs to kill, to murder, to assassinate, to execute and to massacre. The linguistic data are borrowed from the British National Corpus.